The Potency of Microalgae as a Marine Source: A Bibliometric Analysis - Witasari, Hardi Astuti; Kintoko, Kintoko; Ahda, Mustofa; Rangkuti, Ahmad Faizal; Suhendra, Suhendra; Mahfudh, Nurkhasanah (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2025)
Microalgae were a marine source that was highly sustainable and offered numerous benefits in industrial applications. Many species were safe and effective as active ingredients in the food, cosmetics, and pharmacy industries and became raw materials for renewable energy, such as biofuel. The exploration of bioactive compounds was enticing for the research. The study of microalgae potency is a fascinating subject that deserves further exploration. The bibliometrics analysis can provide a good overview of microalgae research and its applications in industry. This overview was derived from the Scopus database, which contained all articles published between 1993 and 2023 with the keywords